2012
DOI: 10.3390/molecules171112704
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Novel Dispirooxindole Derivatives via One-Pot Three-Component 1,3-Dipolar Cycloaddition Reactions

Abstract: A series of novel dispirooxindoles have been synthesized through three-component 1,3-dipolar cycloaddition of azomethine ylides generated in situ by the decarboxylative condensation of isatin and an α-amino acid with the dipolarophile 5-benzylidene-1,3-dimethylpyrimidine-2,4,6-trione. This method has the advantages of mild reaction conditions, high atom economy, excellent yields, and high regio- and stereo-selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…and C5, the latter being the most studied position. Within these structural modifications, various cyclization reactions at C5 and C6 of BA, thiobarbituric acid (TBA) and their derivatives (BADs and TBADs, respectively) [10][11][12][13][14][15][16][17][18][19] as well as at C5 with spiro formation [20][21][22][23][24] have been described. Interestingly, some of these transformations involve a multicomponent reaction (MCR) [11,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…and C5, the latter being the most studied position. Within these structural modifications, various cyclization reactions at C5 and C6 of BA, thiobarbituric acid (TBA) and their derivatives (BADs and TBADs, respectively) [10][11][12][13][14][15][16][17][18][19] as well as at C5 with spiro formation [20][21][22][23][24] have been described. Interestingly, some of these transformations involve a multicomponent reaction (MCR) [11,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pyrazole derivatives 5 , 9 , and 14 have controlled growth of pieces of tumors through their combination with triphosphate, and extension during replication leads to lesions and disruptions on DNA strands (Scheme ) . The same mechanism occurred in the 2‐pyrimidinthione derivatives 6 , 11 , and 15 , same with compounds 5 , 6 , 9 , 11 , 15 , and 16 .…”
Section: Resultsmentioning
confidence: 90%
“…It was previously reported that the thermal and microwave reflux of chalcone 1 with diversity of active methylene, for instance, ethyl cyanoacetate, ethyl acetoacetate, and diethyl malonate with ammonium acetate, produced the pyridine esters 2a–c and 2‐pyridone derivatives 3a–c in good yield that were outlined in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The 1,3‐dipolar cycloaddition of azomethine ylide with dipolarophile is the key of many research groups. 1,3‐Dipolar cycloaddition is potential synthetic applications of many compounds such as incorporation of pentafluorosulfanyl group into isoxazoles and isoazolines , lactams, indolizidines, alkaloids , dispirooxindolopyrrolidines , pyrrolines, pyrrolidines , benzopyranopyrrolidines , pyrrolidinyl oxindoles , and dispirooxindolecyclo[pyrrole(1,2‐c)thiazole‐6,5̍‐thiazolidine] derivatives . In the present research, we have examined a new example of a 1,3‐dipolar cycloaddition between azomethine ylide with dipolarophile with a highly electron rich alkene.…”
Section: Introductionmentioning
confidence: 99%